2014
DOI: 10.7763/ijmmm.2014.v2.121
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Rice Husks Fiber Reinforced Polyester Composites

Abstract: Abstract-Indonesia as a tropical agricultural country has great potential to develop and utilize fiber derived from agricultural waste. Rice husks are an important by-product of rice milling process that can be used as reinforcement in composite products. The purpose of this study was to examine the mechanical properties of rice husks fiber polyester composites. Composites were produced with unsaturated polyester resin as the matrix and rice husks as fiber. The matrix type is polyester Yukalac 157 BQTN, and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…The hybrid composites are a kind of fibre-reinforced materials; it is usually resin-based, in which two different fibres are integrated into a single matrix [10]. The simple theory of composite is of combining two or more materials to get the required properties of materials.…”
Section: Composite Fibre Materialsmentioning
confidence: 99%
“…The hybrid composites are a kind of fibre-reinforced materials; it is usually resin-based, in which two different fibres are integrated into a single matrix [10]. The simple theory of composite is of combining two or more materials to get the required properties of materials.…”
Section: Composite Fibre Materialsmentioning
confidence: 99%
“…The agriculture-plant waste, prepared as bio organic particles, is currently the best suitable, inexpensive and eco-friendly material for the fabrication of advanced composite materials. Many researchers have reported the use of bagasse, dust, rice husk, nano fly ash and coconut shells as filler materials in fabricating polymer composites [11][12][13][14][15][16] , in nature mineral fillers were added in the resin and applied on the fiber, showed increase in the mechanical behavior [17,18] . The determination of Sugarcane bagasse in the form of ash particles and suggested that it be used as fillers in cement and clay bricks, due to its being rich in crystalline silica [19] .…”
Section: Introductionmentioning
confidence: 99%
“…Composite material has wide range in industrialization and engineering fields using appropriate material such as metal, polymers and ceramics so as to obtain optimum features, these materials are being used according to the growing need of the society [1,2]. in the last ten years, the natural fibers reinforcement of polymer composites with have received ever-increasing attention, both of the academic field and different manufactories.…”
Section: Introductionmentioning
confidence: 99%
“…Natural fibers are majorly used with thermoplastics and thermoset plastics. Thermoplastics and thermoset polymers both are non-bio degradable but thermoplastics are recycled in an easy manner as compared to thermoset [1,2,6] The most important merit of natural fiber is biodegradability and noncarcinogenic which get it back into its original form, with an feature of being low cost-effective [6,12,13].…”
Section: Introductionmentioning
confidence: 99%